Combine like terms

My method for of combining like terms for BEGINNERS

Example: 6b + 7b - 10 =

Step 1: Put parentheses around EVERY term; (6b) + (7b) - (10) =

Step 2: Replace all subtraction symbols with an addition symbol AND put a negative symbol INSIDE the parentheses of the term; (6b) + (7b) + (-10) =

Step 3: If necessary, move the "b" terms so that they are together; Not necessary in this case.

Step 4: Add the "b" terms together; (13b) + (-10) =

Step 5: Add the "number" terms; Not necessary because there is only one "number" term.

Step 1: Put parentheses around EVERY term; (6b) + (7b) - (10) =

Step 2: Replace all subtraction symbols with an addition symbol AND put a negative symbol INSIDE the parentheses of the term; (6b) + (7b) + (-10) =

Step 3: If necessary, move the "b" terms so that they are together; Not necessary in this case.

Step 4: Add the "b" terms together; (13b) + (-10) =

Step 5: Add the "number" terms; Not necessary because there is only one "number" term.

Step 6: Remove parentheses; 13b - 10

Another example in which ALL the steps are necessary: -6b + 2 + 7b - 10 =

Step 1: -(6b) + (2) + (7b) - (10) =

Step 2: (-6b) + (2) + (7b) + (-10) =

Step 3: (-6b) + (7b) + (2) + (-10) =

Step 4: (1b) + (2) + (-10) =

Step 5: (1b) + (-8) =

Step 6: b - 8

Step 1: -(6b) + (2) + (7b) - (10) =

Step 2: (-6b) + (2) + (7b) + (-10) =

Step 3: (-6b) + (7b) + (2) + (-10) =

Step 4: (1b) + (2) + (-10) =

Step 5: (1b) + (-8) =

Step 6: b - 8

Special note: 1b = b

I hope this helps you.

## Comments

Thank you for your help!